Measurement of Characteristics of PU/MWNT Films made of Modified MWNT by Dry Heat Treatment (Journal of Fiber Bioengineering and Informatics, 2018)
This study examines the electrical conductivity of multi-walled carbon nanotube (MWNT) /polyurethane (PU) nanocomposites film according to the dispersion conditions. For this purpose, various kinds of polyurethane block copolymer (PU)/multi-wall carbon nanotube (MWNT) with different MWNT contents were mixed and dispersed, and their characteristics related to the dispersion were investigated. Multi-walled carbon nanotubes (MWNT) are of interest in many areas of nanotechnology and used in a number of novel applications. However effective dispersion remains a problem and one solution is to functionalize the nanotubes. In this work, MWNTs are functionalized using an oxidative technique, including dry thermal treatment. The dispersion variation of the PU/MWNT nanocomposite films with MWNT content ranging from 0.1 ∼ 5.0 wt% was examined. The various characteristics of the dispersed PU/MWNT nanocomposite film were characterized using thermo gravimetric analyser (TGA), scanning electron microscope (SEM) and measuring instrument of electrical conductivity. The degree of dispersion of PU/MWNT nanocomposite films according to the dispersion conditions was shown in various situations. The bad dispersion of PU/MWNT film was revealed during the phase separation between PU matrix and MWNT. Also PU/MWNT nanocomposite film shows good electro-conductivity on its surface because MWNT was collected on the surface of composite film due to its low density.